INFLUENCE OF IRRIGATION METHODS AND REGIMES OF WINTER WHEAT VARIETIES ON THE AGROCHEMICAL PROPERTIES OF SOILS UNDER TYPICAL SIEROZEM CONDITIONS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
In the conditions of typical sierozem soils of the Fergana region, subjected to irrigation erosion (slope level 1.50), data on the agrochemical properties of the soil, depending on the irrigation regime and methods of winter wheat varieties Davr and Vexa, are presented.